Energy loss fromneutrino oscillations in massive stars / Nor Sofiah Ahmad - Ahmad, Nor Sofiah (2014)
When neutrinos propagate through a medium and interact with the electrons, an effective potential energy is produced due to the coherent forward scattering. This potential engenders significant changes in the neutrino masses and their mixing in the medium. Thus electron neutrinos would oscillate into a different mass eigenstate and this is dependent on the energy of the neutrinos. Some of the energy will be lost in the coherent scattering with the electrons by the charged current interaction. We have calculated the energy loss of the neutrinos by using a stopping power equation for both non-rotating and rotating 20M⊙ and 120M⊙ stellar models. The total energy loss of the neutrinos depends on the electron number density ne in the stars and on the survival probability of the electron neutrino Pne→ne . For higher ne and the survival probability, the energy loss will be significant. These models are generated by using the Geneva code and post-processed to include the oscillation effect. From these models, we obtain the value of the thermal neutrino energy loss, density of matter and ne used the stopping power equation of matter for neutrinos. We found that the neutrino energy loss of the rotating 20M⊙ model is the highest by six orders of magnitude than the non-rotating 20M⊙ model (∼ 1017 MeV/cm3/s) dominated by the bremsstrahlung process. For the 120M⊙, model the maximum neutrino energy loss is about the same at ∼ 1010 MeV/cm3/s and monopolised by the pair-neutrino process. Overall, the neutrino energy loss due to oscillation is ∼ 1% from the neutrino energy loss without oscillations.